Prevalence of Escherichia coli O157:H7 in Organically and Naturally Raised Beef Cattle - Reinstein, S.; Fox, J. Trent; Shi, X.; Alam, M. J.; Renter, David G.; Nagaraja, Tiruvoor G. (My University, 2009)
We determined the prevalence of Escherichia coli O157:H7 in organically and naturally raised beef cattle at slaughter and compared antibiotic susceptibility profiles of the isolates to those of isolates from conventionally raised beef cattle. The prevalences of E. coli O157:H7 were 14.8 and 14.2% for organically and naturally raised cattle, respectively. No major difference in antibiotic susceptibility patterns among the isolates was observed.